Anthraquinone Derived Cholesterol Linked Imidazole Gelator in Visual Sensing of Picric Acid. Issue 17 (14th June 2017) - Mondal, Subhendu; Ghosh, Kumaresh
Abstract: Anthraquinone derived cholesterol linked imidazole1 has been designed and synthesized. The extensive π‐stacking exerted by aromatic surface and the hydrophobic interaction from cholesterol surface tune the molecular aggregation in solvents like benzene, toluene, 1, 2‐dichlorobenzene and nitrobenzene that results in gelation. Nongelation behaviour of compound2, devoid of cholesterol motif, signifies the role of cholesterol surface in self aggregation. In the presence of 2 equiv. amounts of PA, the The nitrobenzene gel selectively recognizes picric acid over various phenolic and nitroaromatic substrates by exhibiting gel‐to‐sol transition with distinguishable color change from reddish brown to yellow. In CH3 CN containing 1 % THF, compound1 also shows significant fluorometric response toward picric acid over other analytes studied through selective quenching of emission and color change (green to light green in fluorescence and colorless to yellow in UV‐vis). Abstract : Cholesterol coupled anthraquinone‐benzimidazole conjugate1 has been designed and synthesized. The nitrobenzene gel of1 selectively recognizes picric acid by exhibiting gel‐to‐sol phase transition with distinguishable color change from reddis brown to yellow.